2020
DOI: 10.2478/adms-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Research of 316L Metallic Powder for Use in SLM 3D Printing

Abstract: Abstract3D metal printing is an increasingly popular production of steel parts. The most widespread and most accurate method is SLM (Selective Laser Melting), which uses metallic powder as the input material. The article is dedicated to researching the supplied powder from Renishaw. The powder is made by gas atomization and 3 phases of powder (virgin, sift and waste) that are present in the SLM process are examined. Powder morphology by SEM electron microscopy is investigated and the porosity of the powder is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The surfaces of the recycled powders also appear rougher compared to the initially smooth virgin powders. In addition, fine particles called satellites (<5 µm) are attached to the surface of the virgin 316L SS and AlSi10Mg powders (e.g., dashed arrows of the zoomed areas in Figure 1a,d), which is common in virgin metallic powders produced by the gas atomization process [37,42,68]. However, fewer satellites are observed in both recycled powders as shown in Figure 1b,d, often attributed to their detachment from the surface of unmelted powder particles when they are being blown off from the as-built AM parts [27,55,67].…”
Section: Morphology and Distributionmentioning
confidence: 99%
See 4 more Smart Citations
“…The surfaces of the recycled powders also appear rougher compared to the initially smooth virgin powders. In addition, fine particles called satellites (<5 µm) are attached to the surface of the virgin 316L SS and AlSi10Mg powders (e.g., dashed arrows of the zoomed areas in Figure 1a,d), which is common in virgin metallic powders produced by the gas atomization process [37,42,68]. However, fewer satellites are observed in both recycled powders as shown in Figure 1b,d, often attributed to their detachment from the surface of unmelted powder particles when they are being blown off from the as-built AM parts [27,55,67].…”
Section: Morphology and Distributionmentioning
confidence: 99%
“…In addition, the agglomeration of small powder particles on the larger ones could be observed for the recycled 316L SS, as shown in Figure 1b. Such agglomerates are typically caused by the spattering of unmelted powders (powder spatter) from the powder bed upon contact with the laser heat source during SLM fabrication, which are then attached to other unconsolidated or semi-consolidated powder particles [36][37][38]47]. Similarly, other studies have shown that such agglomerates could also arise from melted powder particles that are ejected from the powder bed (droplet spatter), which eventually solidify during the flight and then either adhere to the as-fabricated part or impinge on other powder particles [69][70][71][72].…”
Section: Morphology and Distributionmentioning
confidence: 99%
See 3 more Smart Citations